2022
DOI: 10.1590/s0004-2803.202203000-62
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Severity of Liver Involvement in Hypertensive Disorders of Pregnancy

Abstract: Background: Pre-eclampsia (PE) and eclampsia (E) are among the leading causes of maternal and fetal morbidity and mortality. Both are associated with an evolving spectrum of liver disorders. Objective: The aim of this study was to evaluate the frequency and severity of liver involvement in pregnant women admitted to an intensive care unit with PE/E and to assess its influence on adverse maternal and fetal outcomes. Methods: All subjects, hospitalized between January 2012 and March 2019, were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…A pré-eclâmpsia (PE) e a eclâmpsia (E) estão entre as principais causas de morbidade e mortalidade materna e fetal e, ambas, estão associadas a um espectro evolutivo de distúrbios como alterações da coagulação, hemólise, enzimas hepáticas elevadas, e síndrome de baixa contagem de plaquetas (HELLP). A insuficiência hepática aguda, hematomas subcapsulares hepático e esplênico e infarto hepático podem estar associados (Oliveira et al, 2022).…”
Section: Contextualização Da Problemáticaunclassified
“…A pré-eclâmpsia (PE) e a eclâmpsia (E) estão entre as principais causas de morbidade e mortalidade materna e fetal e, ambas, estão associadas a um espectro evolutivo de distúrbios como alterações da coagulação, hemólise, enzimas hepáticas elevadas, e síndrome de baixa contagem de plaquetas (HELLP). A insuficiência hepática aguda, hematomas subcapsulares hepático e esplênico e infarto hepático podem estar associados (Oliveira et al, 2022).…”
Section: Contextualização Da Problemáticaunclassified
“…Those results reinforce the importance of physical activity in the management of patients with cirrhosis to prevent malnutrition and frailty. Oliveira et al (19) have reported that quite half of those patients with pre-eclampsia and eclampsia have abnormal liver enzymes when admitted to the ICU, usually outside the spectrum of HELLP syndrome. Maternal and fetal mortality was negligible and few have developed life-threatening liver related complications.…”
mentioning
confidence: 99%
“…(33) También observaron en este estudio retrospectivo anomalías de AST y/o ALT en la mitad de los pacientes, la mayoría de ellos tenían ligeras elevaciones de las enzimas hepáticas hasta cinco veces el límite superior normal, pero el 12 % mostró fluctuaciones moderadas a severas de AST y/o ALT. (34) Recuento plaquetario y LDH en las pacientes normotensas y preeclámpticas se obtuvo una p. que es estadísticamente significativa como se esperaba encontrar más disminuidas las plaquetas y las LDH incrementadas que es parte de las complicaciones maternas en la preeclampsia (11) los valores de creatinina en pacientes normotensas y preeclámpticas al igual que en las mujeres preeclámpticas con y sin signos de severidad no hubo una p estadísticamente significativa lo que nos indica que no hubo complicaciones renales.…”
Section: Discussionunclassified